(untitled) (Minerva, 2021)
Building upon his own experience as editor of Liber medicine ex quadrupedibus, an early medieval animal recipe book, the author reflects on the difficulty of detecting archetype errors in compilation texts with an updating tradition, as well as on the criteria to correct them. In particular, several recently proposed corrections to this text are discussed.